At Home Baby First Words (Parragon Thailand, 2001)
"At Home: Baby's First Words" is a charming board book designed to introduce young children to basic vocabulary related to home life. Featuring colorful illustrations and simple, clear text, the book highlights common objects and concepts found around the house, such as "chair," "table," "kitchen," and "bedroom."